FAKTOR-FAKTOR YANG MEMPENGARUHI KECENDERUNGAN KECURANGAN AKUNTANSI (FRAUD) - Luthfi, Muhammad; Puspita, Indah Lia; Sulistya, Novi (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2019)
Fraud is a intentionally fault which could harming many people. In government sector,fraud is harming for public. This research is aimed to explore the influence of factors that impactfraud such as individual morality, internal control government system, accounting rules, motivationand law enforcement. Population research of as many as 90 employees by the respondent governmentagencies working in finance at the Department of subsection Tanggamus Regency. This research usesthe questionnaries to collect the data. Data analysis in this research using analysis structural equationmodeling  with a smart PLS 3.0.The findings of the research showed that there is a negative effectbeetwen individual morality and accounting rules with fraud, there is a positive effect betweenmotivation with fraud, there is no effect between internal control government system with fraud.Keywords: Individual Morality, Internal Control Government System, Accounting Rules andMotivation.